Self-assembled dextrin nanogel as protein carrier: controlled release and biological activity of IL-10 - Carvalho, Vera (2011)
Interleukin-10 (IL-10) is an anti-inflammatory cytokine, which active form is a non-covalent homodimer. Given the potential of IL-10 for application in various medical conditions, it is essential to develop systems for its effective delivery. In previous work, it has been shown that a dextrin nanogel effectively incorporated and stabilized rIL10, enabling its release over time. In this work, the delivery system based on dextrin nanogels was further analyzed. The biocompatibility of the nanogel was comprehensively analyzed, through cytotoxicity (lactate dehydrogenase release, MTS, Live and Dead) and genotoxicity (comet) assays. The release profile of rIL-10 and its biological activity were evaluated in vivo, using C57BL/6 mice. Although able to maintain a stable concentration of IL-10 for at least 4 hours in mice serum, the amount of protein released was rather low. Despite this, the amount of rIL-10 released from the complex was biologically active inhibiting TNF-α production, in vivo, by LPSchallenged mice. In spite of the significant stabilization achieved using the nanogel, rIL-10 still denatures rather quickly. An additional effort is thus necessary to develop an effective delivery system for this cytokine, able to release active protein over longer periods of time. Nevertheless, the good biocompatibility, the protein stabilization effect and the ability to perform as a carrier with controlled release suggest that self-assembled dextrin nanogels may be useful protein delivery systems.